Contract cheating in Z generation: Sociology of education review of academic fraud in Indonesia - Deyanggi Bhinekaswathi; Elly Malihah Setiadi; Yadi Ruyadi (Universitas Negeri Yogyakarta, 2023)
Today, Z Generation around the world including Indonesia have engaged in a form of academic fraud namely “contract cheating”. It is a phenomenon that occurred when students ask others to finished the assignments which is given by their teachers or lecturers. Contract cheating is a serious problem as it relates to educational norms and ethics. The research focuses on contract cheating that occurs on social media among generation Z in Indonesia by offering views that adopt the sociology of education. Technical data collection is carried out by means of documentation to social media such as Intagram, Twitter, and Telegram as well as reviewing book libraries, journals, and websites. The results of the research suggest that 1) contract cheating is a type of academic fraud; 2) students who engage in contract cheating are violating academic norms and ethics; and 3) improvements to the education system are needed to address the problem of contract cheating.